The Role of Cloud Computing in Higher Education: Analysis of Models, Benefits, and Challenges - Abdullah Abdalsalam Abdasameea; Tahr Salem Daduch; Mohammed Abdumutaleb Mawloud (African Journal of Advanced Pure and Applied Sciences, 2025)
Cloud computing has transformed the digital environment, providing dynamic, scalable, and cost-effective IT infrastructure across multiple sectors, including education. This paper investigates the impact of cloud computing in higher education, focusing on its definitions, models, benefits, and challenges. It examines how educational institutions employ cloud services to enhance teaching, research, and administration while addressing issues of security, cost, and accessibility. Using a synthesis of recent scholarly and industry sources, the study underscores the revolutionary potential of cloud technologies in promoting innovation, collaboration, and efficiency. Ultimately, the study concludes that strategic adoption of cloud computing enhances institutional agility and drives sustainable digital transformation in higher education.